Modélisation de l’éco-accompagnement en temps de crise - Patricia Rached (Éducation et Socialisation)
This article addresses the issue of supporting higher-education students in times of crisis. Based on the various paradigmatic perspectives, this study examines accompaniment in a context that integrates the praxeological aim linked to experience and that of heuristics related to scientific knowledge. Subsequently, the synergy between the relevant theories and practices on accompaniment is deployed via social practices following participatory approaches implemented in the Lebanese context that has been enduring a series of severe crises. In the end, the alliance of knowledge and expertise leads to the modeling of an eco-accompaniment system that is part of a chronosystemic paradigm that revolves around five interdependent dimensions : epistemological, pragmatic, axiological, institutional, and strategic. A model that favors the emancipation of the person, the community, and the institution as well.